Two Legged Walking Robot - Kraus, V. (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2015)
The aim of this work is to construct a two-legged wirelessly controlled walking robot. This paper describes the construction of the robot, its control electronics, and the solution of the wireless control. The article also includes a description of the application to control the robot. The control electronics of the walking robot are built using the development kit Arduino Mega, which is enhanced with WiFi module allowing the wireless control, a set of ultrasonic sensors for detecting obstacles in the robot`s surroundings and accelerometer for maintaining balance.
Keywords: Two legged robot; servo; Arduino; wireless module; sensors; Wi-Fi; accelerometer